Relationship between Dietary Habit, Physical Exercise and Medication Adherence to Controlling Blood Sugar Levels at Herna Hospital Medan - Sinaga, Martaulina; Tarigan, Imarina; Yuni, Deby Cintia (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Diabetes mellitus (DM) is a disease with impaired metabolism, fat, and protein caused by reduced insulin secretion or decreased sensitivity insulin. Cases of DM in Herna Hospital in 2017 were 156 cases with the condition where the blood glucose levels are above normal, namely> 200 ml/dl and eating patterns that were not suitable for DM sufferers, not doing physical exercise, and non-adherence taking medicine. This study aims to determine the relationship of diet, physical exercise, and taking medicine to DM at Herna Hospital Medan. This research is a cross-sectional study, with sample 68 DM people. Primary data were obtained using a questionnaire, data analysis was performed using logistic regression analysis. The relationship between diet habit, physical exercise and taking medicine on KGD control, based on the probability value (p) at the significance level a = 0,05. The results showed that there was a correlation between calorie intake and KGD control in DM with RP = 3.12; 95% CI (1.0-9.0) type of food Rp = 4,57; 95% CI (2,1-9,7), meal schedule Rp = 4,57; 95% CI (2,1-9,7) and compliance in drug administrator medicines Rp = 2,29; 95% CI (1.0-5.2) is associated with uncontrolled blood sugar levels (KGD> 200 g / dl) in DM. Based on the results of the analysis concluded that there are a number of calories, types of food, meal schedule and taking medicine in DM patients. Sent to Herna Hospital Medan to improve promotion strategies on DM diet, physical exercise and taking medicine, as well as making nutritional counseling.